Preparation method and application of high-rate type lithium iron phosphate cathode material

CN118495496BActive Publication Date: 2026-10-27HUBEI XINGFA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410672583.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-27
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

[0004]本发明目的在于提供一种高倍率型磷酸铁锂正极材料的制备方法及应用,以解决现有技术中磷酸铁锂作为锂离子电池材料倍率性能较差的技术问题

Benefits of technology

(1)本发明使用碳-氮预聚物对磷酸铁锂前驱体进行均匀负载后,利用预聚物包含的大量亲水性基团对稀土氧化物进行吸附,使稀土氧化物均匀完整地包覆于前驱体表面。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118495496B_ABST
    Figure CN118495496B_ABST
Patent Text Reader

Abstract

The application provides a high-rate lithium iron phosphate positive electrode material and a preparation method thereof. The application comprises the following steps: mixing a lithium source, a phosphorus source, an iron source and a dopant, sand grinding, spray drying and calcining to obtain lithium iron phosphate; reacting the lithium iron phosphate with an indole-3-formaldehyde solution and a compound containing an amino group under acidic conditions, spray drying to generate LFP / C / N, ultrasonic dispersion of the LFP / C / N and rare earth oxide and re-calcining to obtain a high-rate lithium iron phosphate positive electrode material coated with rare earth oxide, wherein ReO2 is uniformly coated on the surface of the lithium iron phosphate positive electrode material. The ReO2 coating layer is always in a stable state, thereby effectively inhibiting the reaction between the lithium iron phosphate active material and the electrolyte to generate by-products, improving the capacity retention rate and cycle life of the battery. The ReO2 coating layer has a low Li + diffusion barrier, which can effectively improve the Li + diffusion rate, and the hybrid layer composed of ReO2 and carbon / nitrogen material can effectively inhibit the polarization generated in the battery charging and discharging process, thereby enhancing the rate performance of the lithium iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium iron phosphate material preparation technology for lithium-ion battery cathode materials, specifically relating to the preparation and application of a high-rate performance lithium iron phosphate composite cathode material. Background Technology

[0002] Lithium iron phosphate (LiFePO4) cathode materials with an olivine structure have significant advantages in power battery materials due to their high safety, cycle stability, and environmental friendliness. They meet the requirements of automotive companies for high safety and high electrical performance electrode materials, and are therefore considered one of the most ideal cathode materials in the power battery field. However, the lithium-ion diffusion rate of LiFePO4 material is only about 10⁻⁶. -14 ~10 -16 The low rate performance (cm / S) results in poor rate performance. Furthermore, during charging and discharging, the interface of the positive electrode material of the lithium-ion battery will produce corresponding side reactions with the electrolyte, which will lead to an increase in battery impedance and a decrease in capacity, further reducing rate performance and affecting cycle capacity retention.

[0003] To improve the rate performance of lithium-ion batteries and further enhance their cycle capacity retention, cathode material surface coating technology has emerged. Its function is to form a barrier on the surface of the cathode material, preventing side reactions between the active material and the electrolyte. Furthermore, it significantly improves the material's conductivity, thereby enhancing its rate performance. Currently, the most common coating material is carbon coating, which avoids direct contact between the cathode material and the electrolyte while improving conductivity. However, carbon coating affects the compaction density of the cathode material and cannot meet the requirements for high-rate charging and discharging. Rare earth oxides, on the other hand, possess extremely high stability, maintaining the three-dimensional electron transition network even under high-rate conditions, ensuring the stability of the material structure. Simultaneously, rare earth oxides have low Li- content... + Diffusion barrier, which is favorable to Li + Furthermore, the combination of rare earth oxides with carbon / nitrogen materials is also an excellent ion and electron conductor, which successfully improves the electron and ion transport capabilities of LFP materials, thereby further enhancing the rate performance and cycle capacity retention of the materials. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing and applying a high-rate lithium iron phosphate cathode material, so as to solve the technical problem that lithium iron phosphate has poor rate performance as a lithium-ion battery material in the prior art.

[0005] The technical solution of the present invention is as follows: A method for preparing a high-rate lithium iron phosphate cathode material includes the following steps: S1: Add lithium source, iron source, phosphorus source and dopant to deionized water to obtain mixture A. Grind mixture A using a sand mill to obtain lithium iron phosphate slurry. Spray dry the lithium iron phosphate slurry and calcine it under an inert atmosphere to obtain substance B. S2: Disperse substance B and indole-3-carboxaldehyde solution in deionized water, heat and stir to obtain suspension C; S3: Add an amino-containing compound to suspension C and formic acid, stir continuously to obtain a suspension, wash the suspension with deionized water by centrifugation, and dry to obtain mixture D; S4: Add mixture D and rare earth oxides to deionized water, ultrasonically disperse to obtain mixture E, and spray dry to obtain precursor F. Calcine the precursor under an inert atmosphere to finally obtain high-rate LFP / C / N@ReO2 cathode material.

[0006] In step S1, the lithium source includes one or more of lithium carbonate, lithium hydroxide, and lithium citrate; the iron source includes one or more of iron phosphate, ferric oxide, and ferrous oxalate; the phosphorus source includes one or more of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; and the dopant includes one of titanium nitrate, titanium carbide, and ammonium metavanadate. The principle is to dope the lithium iron phosphate crystal, thereby changing its cell parameters and shortening the Li... + The transport path is improved, thereby enhancing the electrochemical performance of the material; the molar ratio of lithium source, phosphorus source and iron source is 1~1.1:0.85~1.0:0.9~1.0; the amount of dopant added is 0.3%~0.6% of the mass of the iron source; the calcination temperature is 680~730 ℃; and the holding time is 7~10 h. In step S2, the amount of indole-3-carboxaldehyde solution added is 20%~30% of the mass of substance B, the mass ratio of deionized water to substance B is 2~2.5:1, and the stirring temperature is 60~80 ℃.

[0007] In step S3, the amino-containing compound is one of melamine, dicyandiamide, and urea, and the amount added is 25% to 30% of the mass of the indole-3-carboxaldehyde solution. Formic acid can promote the pH value of the solution to be in the range of 5 to 6 and promote the reaction to proceed, shortening the reaction time to 40 to 60 min, so that indole-3-carboxaldehyde and the amino-containing compound can react completely to generate hydroxymethyl compound. The hydroxymethyl compound generates a cross-linked network structure through condensation reaction under acidic conditions and is uniformly loaded onto the surface of lithium iron phosphate precursor.

[0008] In S4, ReO2 is one of La2O3, Sm2O3, Nd2O3, and Y2O3. This is primarily because rare earth oxides possess extremely high stability, effectively preventing side reactions between the active material and the electrolyte, thus improving the battery's cycle life. Secondly, it can inhibit abnormal growth of lithium iron phosphate grains during high-temperature sintering, thereby obtaining fine and uniform primary particles and improving the material's rate performance. The amount of ReO2 added is 0.2-0.7% of the mass of substance B. The ultrasonic dispersion time is 20-30 minutes, allowing ReO2 to be uniformly adsorbed onto the surface of the LFP / C / N precursor until it completely coats the precursor particles. The calcination temperature is 600-650 ℃, and the holding time is 4-7 hours.

[0009] Another aspect of the present invention provides a high-rate lithium iron phosphate cathode material, wherein rare earth oxides are used as a coating layer, the coating layer thickness is about 2~4 nm, and the primary particle size range of the coated LFP / C / N is 100~300 nm.

[0010] The application of the high-rate lithium iron phosphate material is mainly in lithium-ion battery cathode materials and the batteries and devices assembled from them.

[0011] The beneficial effects of this invention are as follows: (1) In this invention, after uniformly loading the lithium iron phosphate precursor with carbon-nitrogen prepolymer, the rare earth oxides are adsorbed by the large number of hydrophilic groups contained in the prepolymer, so that the rare earth oxides are uniformly and completely coated on the surface of the precursor.

[0012] (2) This invention uses rare earth oxides as a coating layer, which has extremely high stability. Even under high magnification conditions, it can still fix the three-dimensional electron transition network. At the same time, rare earth oxides have low Li + Diffusion barrier, which is favorable to Li + The diffusion of [something] improves the conductivity of lithium iron phosphate cathode materials.

[0013] (3) The rare earth oxide-coated lithium iron phosphate particles are more dispersed, which is conducive to the penetration of electrolyte between particles and ensures the Li + High diffusion rate.

[0014] (4) Rare earth oxides and carbon / nitrogen materials form a highly stable conductive network layer, which connects lithium iron phosphate particles, reduces charge transfer resistance, and further improves the rate performance of lithium iron phosphate. Attached Figure Description

[0015] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 The XRD pattern of the high-rate lithium iron phosphate prepared in Example 1.

[0017] Figure 2 The image shows a SEM image of the high-rate lithium iron phosphate prepared in Example 1.

[0018] Figure 3 This is a rate performance diagram for Example 1.

[0019] Figure 4 This is a cyclic curve diagram of Example 1.

[0020] Figure 5 This is a performance chart for the scaling factor of Comparative Example 1.

[0021] Figure 6 This is a cyclic curve graph for Comparative Example 1.

[0022] Figure 7 This is a performance chart of the scaling factor for Comparative Example 2.

[0023] Figure 8 This is a cyclic curve graph for Comparative Example 2. Specific Implementation The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0025] The process for preparing lithium iron phosphate using the above-mentioned lithium source and iron phosphate is described in the following examples: Example 1 A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.03:1, ammonium metavanadate (0.3% by mass of iron phosphate), and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 680 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 9 h to obtain lithium iron phosphate. A2: Disperse the lithium iron phosphate obtained in step A1 with the indole-3-carboxaldehyde solution in deionized water. The mass of the indole-3-carboxaldehyde solution accounts for 20% of the mass of lithium iron phosphate, and the mass of the deionized water is twice the mass of lithium iron phosphate. Heat to 60 °C and stir for 30 min to obtain a suspension. A3: Melamine, accounting for 25% of the mass of the indole-3-carboxaldehyde solution, was added to the suspension obtained in step A2, and formic acid was added to adjust the pH of the solution to 5. The mixture was stirred for 40 min, centrifuged, and dried to obtain the mixture. A4: Add La2O3 and the mixture obtained in step A3 to deionized water, ultrasonically disperse for 30 min, and then spray dry (air temperature 120 ℃, outlet air temperature 80 ℃) to obtain the precursor, wherein the amount of La2O3 added is 0.2% of the mass of lithium iron phosphate; A5: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ and held for 2 h in a tube furnace at a heating rate of 2 ℃ / min, and then heated to 620℃ and held for 7 h at a heating rate of 5 ℃ / min, finally obtaining a high-rate lithium iron phosphate cathode material.

[0026] Example 2 A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.02:1, titanium nitrate (0.3% by mass of iron phosphate), and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 700 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 7 h to obtain lithium iron phosphate. A2: Disperse the lithium iron phosphate obtained in step A1 with the indole-3-carboxaldehyde solution in deionized water. The mass of the indole-3-carboxaldehyde solution accounts for 25% of the mass of lithium iron phosphate, and the mass of the deionized water is twice the mass of lithium iron phosphate. Heat to 65 °C and stir for 30 min to obtain a suspension. A3: Add 27% of the indole-3-carboxaldehyde solution by weight of dicyandiamide to the suspension obtained in step A2, and add formic acid to adjust the pH of the solution to 5.3. Stir the reaction for 40 min, centrifuge, and dry to obtain the mixture. A4: Add Nd2O3 and the mixture obtained in step A3 to deionized water, ultrasonically disperse for 25 min, and then spray dry (air temperature 120 ℃, outlet air temperature 80 ℃) to obtain the precursor, wherein the amount of Nd2O3 added is 0.4% of the mass of lithium iron phosphate; A5: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ at a heating rate of 2℃ / min and held for 2 h in a tube furnace, and then heated to 640℃ at a heating rate of 5℃ / min and held for 5 h to finally obtain a high-rate lithium iron phosphate cathode material.

[0027] Example 3 A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.02:1, ammonium metavanadate (0.4% by mass of iron phosphate), and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 720 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere. The temperature is held for 8 hours to obtain lithium iron phosphate. A2: Disperse the lithium iron phosphate precursor obtained in step A1 with indole-3-carboxaldehyde solution in deionized water. The mass of indole-3-carboxaldehyde solution accounts for 27% of the theoretical mass of lithium iron phosphate, and the mass of deionized water is 2.5 times the mass of lithium iron phosphate. Heat to 70 °C and stir for 30 min to obtain a suspension. A3: Add urea at 29% of the mass of indole-3-carboxaldehyde solution to the suspension obtained in step A2, and add formic acid to adjust the pH of the solution to 5.8. Stir the reaction for 53 min, centrifuge, and dry to obtain the mixture. A4: Add Sm2O3 and the mixture obtained in step A3 to deionized water, ultrasonically disperse for 30 min, and then spray dry (air temperature 120 ℃, outlet air temperature 80 ℃) to obtain the precursor, wherein the amount of Sm2O3 added is 0.6% of the mass of lithium iron phosphate; A5: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ and held for 2 h in a tube furnace at a heating rate of 2 ℃ / min, and then heated to 650℃ and held for 4 h at a heating rate of 5 ℃ / min, finally obtaining a high-rate lithium iron phosphate cathode material.

[0028] Example 4 A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.04:1, titanium carbide with a mass fraction of 0.6% of iron phosphate, and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the sand mill particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 700 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 7 h to obtain lithium iron phosphate. A2: Disperse the lithium iron phosphate precursor obtained in step A1 with indole-3-carboxaldehyde solution in deionized water. The mass of indole-3-carboxaldehyde solution accounts for 30% of the mass of lithium iron phosphate, and the mass of deionized water is 2.5 times the mass of lithium iron phosphate precursor. Heat to 80 °C and stir for 25 min to obtain a suspension. A3: Melamine, accounting for 30% of the mass of the indole-3-carboxaldehyde solution, was added to the suspension obtained in step A2, and formic acid was added to adjust the pH of the solution to 6. The mixture was stirred for 40 min, centrifuged, and dried to obtain the mixture. A4: Add Y2O3 and the mixture obtained in step A3 to deionized water, ultrasonically disperse for 30 min, and then spray dry (air temperature 120 ℃, outlet air temperature 80 ℃) to obtain the precursor, wherein the amount of Y2O3 added is 0.7% of the mass of lithium iron phosphate; A5: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ and held for 2 h at a heating rate of 2 ℃ / min in a tube furnace, and then heated to 625℃ and held for 6 h at a heating rate of 5 ℃ / min to finally obtain a high-rate lithium iron phosphate cathode material.

[0029] Comparative Example 1: A1: Take lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.03:1, TiO2 with a mass fraction of 0.3% of iron phosphate, and deionized water, and add them to a sand mill to adjust the solid content to 43%. Use the sand mill to grind and mix the above raw materials until the sand mill particle size D50 reaches 200-250 nm. Stop the sand mill and discharge the material to obtain a mixed slurry. A2: The mixed slurry obtained in step A1 is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor; under a high-purity nitrogen atmosphere, it is heated to 200 ℃ in a tube furnace at a heating rate of 2 ℃ / min and held for 2 h, and then heated to 700 ℃ at a heating rate of 5 ℃ / min and held for 8 h to obtain the lithium iron phosphate cathode material.

[0030] Comparative Example 2: A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.03:1, ammonium metavanadate with a mass fraction of 0.3% of iron phosphate, and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the sand mill particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 700 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 7 h to obtain lithium iron phosphate. A2: The lithium iron phosphate obtained in step A1 and La2O3 were dispersed in deionized water, ultrasonically dispersed for 30 min, and then spray-dried (air temperature 120 ℃, outlet air temperature 80 ℃) to obtain the precursor, wherein the amount of La2O3 added was 0.2% of the mass of lithium iron phosphate; A3: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ and held for 2 h in a tube furnace at a heating rate of 2 ℃ / min, and then heated to 620℃ and held for 7 h at a heating rate of 5 ℃ / min, finally obtaining lithium iron phosphate@La2O3 cathode material.

[0031] Comparative Example 3: A1: Lithium carbonate and iron phosphate with a Li / Fe molar ratio of 1.03:1, ammonium metavanadate (0.3% by mass of iron phosphate), and deionized water are added to a sand mill to adjust the solid content to 43%. The above raw materials are ground and mixed using a sand mill until the particle size D50 reaches 200-250 nm. The sand milling is stopped and the mixed slurry is discharged. The mixed slurry is spray-dried at an inlet air temperature of 120 ℃ and an outlet air temperature of 80 ℃ to obtain a lithium iron phosphate precursor. The obtained lithium iron phosphate precursor is placed in a tube furnace and heated to 680 ℃ at a heating rate of 5 ℃ / min under a high-purity nitrogen atmosphere, and held for 9 h to obtain lithium iron phosphate. A2: Disperse the lithium iron phosphate obtained in step A1 with the indole-3-carboxaldehyde solution in deionized water. The mass of the indole-3-carboxaldehyde solution accounts for 20% of the mass of lithium iron phosphate, and the mass of the deionized water is twice the mass of the lithium iron phosphate precursor. Heat to 60 °C and stir for 30 min to obtain a suspension. A3: Melamine, accounting for 25% of the mass of the indole-3-carboxaldehyde solution, was added to the suspension obtained in step A2, and formic acid was added to adjust the pH of the solution to 5. The mixture was stirred for 40 min, centrifuged, and dried to obtain the mixture. A4: Under a high-purity nitrogen atmosphere, the precursor was heated to 200℃ at a heating rate of 2℃ / min and held for 2 h in a tube furnace, and then heated to 620℃ at a heating rate of 5℃ / min and held for 7 h to finally obtain the LFP / C / N cathode material.

[0032] Table 1 Performance Comparison of Different Embodiments

[0033] As can be seen from Table 1, compared with Comparative Examples 1-3, Examples 1-5 show that the rate performance of lithium iron phosphate / carbon / nitrogen cathode materials coated with rare earth oxides is significantly improved, which can effectively solve the problem of poor conductivity of lithium iron phosphate cathode materials.

Claims

1. A method for preparing a high-rate lithium iron phosphate cathode material, characterized in that, The preparation steps include the following: S1: Add lithium source, iron source, phosphorus source and dopant to deionized water to obtain mixture A. Grind mixture A using a sand mill to obtain lithium iron phosphate slurry. Spray dry the lithium iron phosphate slurry and calcine it under an inert atmosphere to obtain substance B. S2: Disperse substance B and indole-3-carboxaldehyde solution in deionized water, heat and stir to obtain suspension C, the amount of indole-3-carboxaldehyde solution added is 20%~30% of the mass of substance B; S3: Add an amino-containing compound to suspension C and add formic acid. Stir continuously to obtain a suspension. Centrifuge and wash the suspension with deionized water and dry it to obtain mixture D. The amino-containing compound includes one of melamine, dicyandiamide and urea. S4: Add mixture D and rare earth oxides to deionized water, ultrasonically disperse to obtain mixture E, and spray dry to obtain precursor F. Calcinate the precursor under an inert atmosphere to finally obtain high-rate LFP / C / N@ReO2 cathode material. The rare earth oxide ReO2 is one of La2O3, Sm2O3, Nd2O3, and Y2O3.

2. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, In step S1, the lithium source includes one or more of lithium carbonate, lithium hydroxide, and lithium citrate; the iron source includes one or more of iron phosphate, ferric oxide, and ferrous oxalate; the phosphorus source includes one or more of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; and the dopant includes one or more of titanium nitrate, titanium carbide, and ammonium metavanadate.

3. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 2, characterized in that, The molar ratio of the lithium source, phosphorus source and iron source is 1~1.1:0.85~1.0:0.9~1.0; the amount of dopant added is 0.3%~0.6% of the mass of the iron source; the calcination temperature is 680~730 ℃; and the holding time is 7~10 h.

4. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, In step S2, the mass ratio of deionized water to substance B is 2~2.5:1, and the stirring temperature is 60~80 ℃.

5. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, In step S3, the amount of amino-containing compound added is 25% to 30% of the mass of the indole-3-carboxaldehyde solution, and the stirring reaction time is 40 to 60 min.

6. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, In step S4, the amount of ReO2 added is 0.2 to 0.7% of the mass of substance B.

7. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, In step S4, the ultrasonic dispersion time is 20-30 min; the calcination temperature is 600-650 ℃, and the holding time is 4-7 h.

8. The method for preparing a high-rate lithium iron phosphate cathode material according to claim 1, characterized in that, The primary particle size distribution of LFP / C / N is 100~300 nm, and ReO2 is used as the coating layer of LFP / C / N with a coating layer thickness of 2~4 nm.

9. A high-rate lithium iron phosphate cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the lithium iron phosphate cathode material as described in claim 9 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Lithium / carbon pyrophosphate coated lithium iron phosphate composite and preparation method thereof

    CN103441269A

  • Fast ion conductor coated lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN115995539A